Dynamic Analysis of Vehicle Track Coupling Based on Double Beam Track Model - Yayun Qi; Huanyun Dai; Jianjin Yang; Kun Xu (Shock and Vibration)
The rail was considered as double Timoshenko beam in this paper, applied to the vehicle track coupling dynamics model; the Hertz nonlinear method is used to calculate the wheel rail contact force. Wheel rail vertical force and response of vehicle are calculated by using the model under random irregularity and single harmonic excitation; at the same time, wheel rail force and vertical acceleration response of 3-order, 10-order, and 19-order wheel polygon were calculated. The results show that, under the excitation of random irregularity, the wheel rail vertical force of two models was very close in the low frequency band, and the response of the double beam model in the high frequency band of 200–1000 Hz is larger than the single beam model, and the acceleration and displacement responses of the double beam model are relatively close. Under a single harmonic excitation, the double beam model has a shorter wheel rail force attenuation time than that of the single beam model. And wheel rail force peak value of double beam model is 9% larger than that of single beam model. Similarly, the vertical displacement of the double beam model increased by 2.6%. Under the 3-order and 10-order wheel polygon excitation, vertical wheel rail peak force of double beam is, respectively, 37.5% and 50% larger than single beam model; the vertical frame acceleration amplitude is 1 g and 1.7 g; under the 19-order polygon wheel excitation, the difference of the wheel rail force between two models is very small, and the amplitude of acceleration of bogie is 2.3 g. And double beam model has more advantage in analyzing high frequency problems such as wheel polygonization.